2021
DOI: 10.3390/biology10100988
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin, Neurokinin B, and Dynorphin Expression during Pubertal Development in Female Sheep

Abstract: The neural mechanisms underlying increases in gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH) secretion that drive puberty onset are unknown. Neurons coexpressing kisspeptin, neurokinin B (NKB), and dynorphin, i.e., KNDy neurons, are important as kisspeptin and NKB are stimulatory, and dynorphin inhibitory, to GnRH secretion. Given this, we hypothesized that kisspeptin and NKB expression would increase, but that dynorphin expression would decrease, with puberty. We collected blood and hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
10
0
1
Order By: Relevance
“…However, no such difference was found during pubertal development in E2‐treated ovariectomized ewes (OVX + E2), both at the level of Kiss1 transcripts 48,49 and kisspeptin immunoreactivity 49 . The choice of conditions (ovary‐intact vs. OVX + E2 females) could explain the divergence of these outcomes 49 . Our results in ovary‐intact pubescent does during the luteal phase are consistent with the observations of Nestor et al 33 Although in female goats the number of kisspeptin‐immunoreactive neurons seems to be greater during the follicular phase than during the luteal phase, 50 the kisspeptin neuronal network may be sufficiently developed to maintain cyclic ovarian activity in pubescent females exposed to sexually active males.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, no such difference was found during pubertal development in E2‐treated ovariectomized ewes (OVX + E2), both at the level of Kiss1 transcripts 48,49 and kisspeptin immunoreactivity 49 . The choice of conditions (ovary‐intact vs. OVX + E2 females) could explain the divergence of these outcomes 49 . Our results in ovary‐intact pubescent does during the luteal phase are consistent with the observations of Nestor et al 33 Although in female goats the number of kisspeptin‐immunoreactive neurons seems to be greater during the follicular phase than during the luteal phase, 50 the kisspeptin neuronal network may be sufficiently developed to maintain cyclic ovarian activity in pubescent females exposed to sexually active males.…”
Section: Discussionmentioning
confidence: 95%
“…In sheep, the number of kisspeptin neurons was higher in the ARC of ovary‐intact pubescent ewes during the early follicular phase (>9 months) compared to prepubescent ewes (5–6 months) 33 . However, no such difference was found during pubertal development in E2‐treated ovariectomized ewes (OVX + E2), both at the level of Kiss1 transcripts 48,49 and kisspeptin immunoreactivity 49 . The choice of conditions (ovary‐intact vs. OVX + E2 females) could explain the divergence of these outcomes 49 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our previous study showed that chronic food restriction (negative energy balance) during the pre-pubertal phase caused suppression of ARC Pdyn and Kiss1 expression and subsequent pubertal failure in growth-retarded female rats and that ad libitum feeding (positive energy cues) caused an acute increase in the number of Pdyn-and Kiss1-expressing cells in the ARC, triggering puberty onset in growth-retarded female rats (Majarune et al, 2019). Similarly, Aerts et al (2021) showed pubertal increases in Pdyn and Kiss1, but not Tac3, expression in the ARC of lambs. These findings suggest that dynorphin-KOR signaling and Kiss1 (as components of KNDy neurons) serve as critical regulators of GnRH pulse generation at the onset of puberty in female mammals.…”
Section: Involvement Of Endogenous Opioid Peptides In Mediating Pre-p...mentioning
confidence: 99%